2011
DOI: 10.1073/pnas.1016472108
|View full text |Cite
|
Sign up to set email alerts
|

Autophagosome targeting and membrane curvature sensing by Barkor/Atg14(L)

Abstract: The class III phosphatidylinositol 3-kinase (PI3KC3) is crucial for autophagosome biogenesis. It has been long speculated to nucleate the autophagosome membrane, but the biochemical mechanism of such nucleation activity remains unsolved. We recently identified Barkor/Atg14(L) as the targeting factor for PI3KC3 to autophagosome membrane. Here, we show that we have characterized the region of Barkor/Atg14(L) required for autophagosome targeting and identified the BATS [Barkor/Atg14(L) autophagosome targeting seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
240
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(253 citation statements)
references
References 39 publications
7
240
0
1
Order By: Relevance
“…Similarly, Atg14L was not reported to localize to any intracellular pathogenassociated compartment, although Atg14L is required for completion of the intracellular life cycle of Brucella (6). Atg14L accumulates on highly curved PI3P-enriched autophagic membrane through its C-terminal Beclin 1-associated autophagy-related key regulator/Atg14L autophagosome targeting sequence domain (37). It was suggested that, when autophagosomes expand by membrane fusion, PI3P is dephosphorylated, which leads to the dissociation of the Atg14L-PI3KC3 complex from autophagosomes (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Atg14L was not reported to localize to any intracellular pathogenassociated compartment, although Atg14L is required for completion of the intracellular life cycle of Brucella (6). Atg14L accumulates on highly curved PI3P-enriched autophagic membrane through its C-terminal Beclin 1-associated autophagy-related key regulator/Atg14L autophagosome targeting sequence domain (37). It was suggested that, when autophagosomes expand by membrane fusion, PI3P is dephosphorylated, which leads to the dissociation of the Atg14L-PI3KC3 complex from autophagosomes (37).…”
Section: Discussionmentioning
confidence: 99%
“…Atg14L accumulates on highly curved PI3P-enriched autophagic membrane through its C-terminal Beclin 1-associated autophagy-related key regulator/Atg14L autophagosome targeting sequence domain (37). It was suggested that, when autophagosomes expand by membrane fusion, PI3P is dephosphorylated, which leads to the dissociation of the Atg14L-PI3KC3 complex from autophagosomes (37). Furthermore, a study proposed that Atg14L and PI3KC3 dissociation from autophagosome might cause membrane curvature instability and prime the membrane for fusion with endosomes-lysosomes (37).…”
Section: Discussionmentioning
confidence: 99%
“…Since the mutation of the cysteine repeat abrogated the autophagy-inducing ability of Atg14L, and the addition of the ER localization sequence from DFCP1 rescued the deficiency, it was concluded that the ER localization of Atg14L is crucial for autophagosome biogenesis [66]. In addition, the C-terminus of mammalian Atg14L, which is also required for its ER localization [66], has been shown to preferentially bind to liposomes containing PI3P or PI(4,5)P2 [67].…”
Section: Autophagosome Formation On the Ermentioning
confidence: 99%
“…142,144 Indeed, the Barkor/Atg14(L) autophagosome targeting sequence/BATS domain of ATG14 has been confirmed to be required for targeting the PIK3C3 complex to the phagophore and/or omegasome membrane and for the initiation of autophagosome formation. 145 Exogenously expressed ATG14 colocalizes with LC3, ATG12 and ATG5, indicating that ATG14 may engage in the recruitment of LC3, ATG12, and ATG5 at an early step of autophagy. 75,77,78 More interestingly, ATG14 likely mediates the differential regulation of PIK3C3 in different class III PtdIns3K complexes.…”
Section: Regulation Of Autophagy By Pik3c3 Via Atg14mentioning
confidence: 99%